A review on plants and microorganisms mediated synthesis of silver nanoparticles, role of plants metabolites and applications - Mustapha, Tijjani; Misni, Norashiqin; Ithnin, Nur Raihana; Muhammad Daskum, Abdullahi; Unyah, Ngah Zasmy (MDPI, 2022)
Silver nanoparticles are one of the most extensively studied nanomaterials due to their high stability and low chemical reactivity in comparison to other metals. They are commonly synthesized using toxic chemical reducing agents which reduce metal ions into uncharged nanoparticles. However, in the last few decades, several efforts were made to develop green synthesis methods to avoid the use of hazardous materials. The natural biomolecules found in plants such as proteins/enzymes, amino acids, polysaccharides, alkaloids, alcoholic compounds, and vitamins are responsible for the formation of silver nanoparticles. The green synthesis of silver nanoparticles is an eco-friendly approach, which should be further explored for the potential of different plants to synthesize nanoparticles. In the present review we describe the green synthesis of nanoparticles using plants, bacteria, and fungi and the role of plant metabolites in the synthesis process. Moreover, the present review also describes some applications of silver nanoparticles in different aspects such as antimicrobial, biomedicine, mosquito control, environment and wastewater treatment, agricultural, food safety, and food packaging.